Penerapan Imajinasi Terbimbing terhadap Kecemasan pada Pasien Preoperasi: Application of Guided Imagery to Anxiety Among Preoperative Patients - Septi Kurniyati; Dwi Retnaningsih (Jurnal Keperawatan Berbudaya Sehat, 2026)
Surgical procedures are invasive interventions that often cause anxiety in patients before surgery. Anxiety experienced by patients, if not managed properly, may affect physiological conditions such as increased blood pressure and heart rate, thereby potentially interfering with the implementation of surgical procedures. The goal of the study to determine the application of guided imagery techniques on anxiety levels in preoperative patients. This study used a case study design involving four preoperative patients as respondents. Anxiety levels were measured using the Amsterdam Preoperative Anxiety and Information Scale before and after the guided imagery intervention, which was conducted for approximately 20 minutes. Data were analyzed descriptively by comparing changes in anxiety scores before and after the intervention. The results showed that the average anxiety score before the intervention was 18, which was categorized as moderate anxiety. After the guided imagery technique was applied, the average anxiety score decreased to 13.5, which was categorized as mild anxiety. All respondents experienced a decrease in anxiety levels after receiving the intervention. Guided imagery techniques can be used as an effective non-pharmacological nursing intervention to help reduce anxiety and improve patients’ psychological readiness before undergoing surgical procedures.